Lower Digit Ratio (2D:4D) Indicative of Excess Prenatal Androgen Is Associated With Increased Sociability and Greater Social Capital - Buchholz, Verena N.; Mühle, Christiane; , Cohort Study on Substance Use Risk Factors; Kornhuber, Johannes; Lenz, Bernd; Gmel, Gerhard; Mohler-Kuo, Meichun; Foster, Simon; Marmet, Simon; Studer, Joseph (Frontiers in Behavioral Neuroscience, 2019)
Positive social interactions are crucial for human well-being. Elevated prenatal exposure to testosterone as indicated by a low second-to-fourth finger length (2D:4D) ratio relates to more aggressive/hostile behaviour in men, especially in challenging situations. The personality trait sociability describes how much people enjoy interacting with others. Given its role in approach and avoidance behaviour, sociability could also be influenced by prenatal sex hormones, but studies thus far have been inconclusive. Here, we investigated the association between 2D:4D ratio and the personality trait sociability, complemented by personal social capital and personal social-network size, in a population-based cohort of 4998 men. Lower 2D:4D ratios was significantly correlated with higher sociability, greater personal social capital, and larger personal social-network size. These effects were consistent across both hands individually and their mean value. Furthermore, two factors of sociability, (1) liking parties and the company of friends and (2) isolation intolerance, were significantly correlated with this prenatal testosterone marker. An exploratory analysis revealed no link between the 2D:4D ratio and responses to the aggression personality trait or items related to anti-social-personality disorder. Our data suggest that prenatal androgen exposure organizes the brain with lasting effects on social behaviour.